Genealogía de la semilla. Regulación y escasez en la Región Pampera de la Argentina - Hendel , Verónica (Nómadas. Critical Journal of Social and Juridical Science, 2010)
Towards the end of the year 2001, the terms hunger and Argentina became synonyms of the crisis of neoliberalism. This article examines the specificity of that danger of hunger that emerges from time to time, and continuous resounding among us. A danger that connects with others and that only by considering those links, that web, we may understand in deep. It is in this sense that hunger, agriculture and population growth amalgam and their boundaries turn vague until they blur. This is one of the reasons why, apart from the fact that we are not interested in analyzing the phenomenon as it may appear in the market, we have chosen a path that lies inside this knowledge-power apparatus (dispositif) and that will become our guide: the seed; that is to say, the source of nutritious potential, life deposit, and food starting point. So, along this article we shall deal with the problem of hunger as scarcity, in its double dimension agriculture/population growth, from the multiple interventions that in Argentina’s case, especially since the 1930s, have emerged in order to deal with the production, use and circulation of seeds in the Pampas Region.
Keywords: Scarcity; Seed; Regulation; Life; Genealogy